The Helags Mountain, Sweden: Another piece in the Caledonian puzzle - Johansson, Sara (Geology, Geophysics and Environment, 2015)
The Scandinavian Caledonides formed due to the closure of the Iapetus Ocean in Ordovician time, a process that likely involved several subduction-eduction events before the subsequent collision between the palaeocontinents Laurentia and Baltica in Silurian and Early Devonian time. However, there are still uncertainties regarding the evolution and timing of the orogenic processes involved in the formation of the Caledonian orogen. To further investigate the time constraints on the key orogenic events, detailed studies of different high-pressure lithologies and mylonites are required. Such high-pressure lithologies are found in Jämtland, central Sweden, to occur in the Lower and Middle Seve Nappe Complex (SNC).This study focus on the metamorphic evolution of the Helags Mountain area, part of the SNC in Jämtland. Preliminary results show that the rocks of this area record a similar history to that of the key locality of Åreskutan Nappe. Studies of the Helags Mountain area can therefore shed further light on the geological history of the Seve Nappe Complex, and can add another piece to the Caledonian puzzle.